Polyendocrinopathy, deafness and albinism, a new combination syndrome - Isaq A. AlMughaizel; Abdulhameed A. Al-Bunyan; Yassin M. Al-saleh; Eman S. AlMoosa; Manal M. Al-Shawi; Yaqoub Y. AlMousa; Fatimah M. AlJishi (Journal of Biochemical and Clinical Genetics)
Background: Waardenburg syndrome is a rare genetic disorder with distinct characteristics. Since their discovery, some types of WS have been reported only once. Type 2F, the subject of this article, has only eleven reported cases worldwide. Case Presentation: In this article, we report a 15-year-old female patient with type 2F who exhibited bilateral sensorineural hearing loss. It is the first reported case of WS type 2F with albinism since birth, type 1 diabetes mellitus (DM), absent internal female reproductive organs, and short stature. Conclusion: In the current case, it might be classified as a new type of WS with this distinguished and unique presentation. Consanguineous marriages might reveal hidden diseased genes. This condition requires a multidisciplinary team management. [JBCGenetics 2024; 7(1.000): 040-049]